Analysis of polar metabolites by hydrophilic interaction chromatography––MS/MS. (April 2011) - Jian, Wenying; Xu, Yaodong; Edom, Richard W; Weng, Naidong
Increasing emphasis has been placed on quantitative characterization of drug metabolites during drug discovery and development. Due to the more polar nature of drug metabolites, quantitative analysis using traditional reversed-phase liquid chromatography tandem mass spectrometry (RPLC––MS/MS) can be quite challenging. As an alternative chromatographic mode, hydrophilic interaction chromatography (HILIC) offers unique advantages for analysis of polar metabolites, providing better retention/separation, higher sensitivity, higher efficiency and potential for ultra-fast analysis to improve throughput. In this article, selected case studies from the authors'' own laboratory, and examples from current literature, will be discussed to demonstrate some practical considerations for method development of HILIC––MS/MS assays. The effectiveness of using HILIC––MS/MS for mitigating analytical challenges associated with quantitation of polar metabolites, including phase I and II metabolites of drugs, as well as endogenous metabolites, will be exhibited.